Case Manager Perspectives on the Role of Treatment in Supportive Housing for People with Severe Mental Illness - Stanhope, Victoria (J Soc Social Work Res, 2016)
OBJECTIVE: Growing recognition exists of housing as a social determinant of health, and thus, health care reform initiatives are expanding the reach of health care beyond traditional settings. One result of this expansion is increased Medicaid funds for supportive-housing programs for people with severe mental illnesses. This qualitative study explores the ways in which case managers working in a supportive housing program approach treatment and how their approach is influenced by both program requirements and their beliefs about mental illness. METHOD: The study is part of a longitudinal qualitative study on recovery for people with severe mental illnesses living in supportive housing. Multiple interviews (n = 55) with 24 case managers from a residential-continuum supportive-housing program were conducted over 18 months. To provide an in-depth view of case manager perspectives, the study uses thematic analysis with multiple coders. RESULTS: Overall, case managers understand supportive housing as being a treatment program but predominantly characterize treatment as medication management. The following themes emerged: believing medication to be the key to success in the program, persuading residents to take medication, and questioning the utility of the program for residents who were not medication adherent. CONCLUSIONS: Case managers understand supportive housing to be a treatment program; however, given the external constraints and their own beliefs about mental illness, case managers often equate treatment with taking medication. Study findings demonstrate the need to train case managers about mental health recovery and integrated health care. The findings also have implications for policies that tie housing to services.